FACTORS RELATED TO THE UTILIZATION OF HEALTH SERVICES IN THE SINUNUKAN HEALTH CENTER IN MANDAILING NATAL DISTRICT OF 2023: FACTORS RELATED TO THE UTILIZATION OF HEALTH SERVICES IN THE SINUNUKAN HEALTH CENTER IN MANDAILING NATAL DISTRICT OF 2023 - thesalonica, Angel; Eviyanti Simanjuntak; Herna Rinayanti Manurung, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Health services are any efforts carried out individually or jointly within an organization to prevent and improve health, maintain and cure disease and restore the health of individuals, groups and families. The aim of the research is to analyze factors related to the utilization of health services at the Sinunukan Community Health Center, Mandailing Natal Regency in 2023. The research method used is descriptive with a quantitative approach and a cross-sectional research design. The sample in this study was residents in the Sinunukan Community Health Center working area, Mandailing Natal Regency. The sample collection method used was the Lameshow formula. The results of statistical tests using Chi Square obtained a p-value = 0.032 (p < 0.05), so Ho was accepted, namely that there was a relationship between age and the use of health services at the Community Health Center. The use of health services by respondents is not only based on the use by the respondents themselves but also by family members of different ages. The results of the statistical test obtained a p-value = 0.01 (P < 0.05), so Ho was accepted so it could be concluded that there was a relationship between education and the use of health services at the Community Health Center. So, it can be concluded that the need for health services can occur regardless of age and education.